Descending projections from the basal forebrain to the orexin neurons in mice. Issue 7 (22nd February 2017) - Agostinelli, Lindsay J.; Ferrari, Loris L.; Mahoney, Carrie E.; Mochizuki, Takatoshi; Lowell, Bradford B.; Arrigoni, Elda; Scammell, Thomas E.
Abstract: The orexin (hypocretin) neurons play an essential role in promoting arousal, and loss of the orexin neurons results in narcolepsy, a condition characterized by chronic sleepiness and cataplexy. The orexin neurons excite wake‐promoting neurons in the basal forebrain (BF), and a reciprocal projection from the BF back to the orexin neurons may help promote arousal and motivation. The BF contains at least three different cell types (cholinergic, glutamatergic, and γ‐aminobutyric acid (GABA)ergic neurons) across its different regions (medial septum, diagonal band, magnocellular preoptic area, and substantia innominata). Given the neurochemical and anatomical heterogeneity of the BF, we mapped the pattern of BF projections to the orexin neurons across multiple BF regions and neuronal types. We performed conditional anterograde tracing using mice that express Cre recombinase only in neurons producing acetylcholine, glutamate, or GABA. We found that the orexin neurons are heavily apposed by axon terminals of glutamatergic and GABAergic neurons of the substantia innominata (SI) and magnocellular preoptic area, but there was no innervation by the cholinergic neurons. Channelrhodopsin‐assisted circuit mapping (CRACM) demonstrated that glutamatergic SI neurons frequently form functional synapses with the orexin neurons, but, surprisingly, functional synapses from SI GABAergic neurons were rare. Considering their strong reciprocal connections, BF and orexin neurons likely work in concert to promote arousal, motivation, and other behaviors. J. Comp. Neurol. 525:1668–1684, 2017. © 2016 Wiley Periodicals, Inc. Abstract : The basal forebrain and orexin neurons are both implicated in arousal and wakefulness. Glutamatergic projections from the substantia innominata (SI) excite the orexin neurons, but GABA projections from the SI appear to be silent. The medial septum (MS) and horizontal nucleus of the diagonal band (HDB) sparsely innervate the orexin neurons.